2009
DOI: 10.1021/nn901252r
|View full text |Cite
|
Sign up to set email alerts
|

Sharper and Faster “Nano Darts” Kill More Bacteria: A Study of Antibacterial Activity of Individually Dispersed Pristine Single-Walled Carbon Nanotube

Abstract: To further our understanding on the antibacterial activity of single-walled carbon nanotubes (SWCNTs), high purity SWCNTs with average diameter of 0.83 nm and (7,5) chirality as dominate (n,m) structure were dispersed in a biocompatible surfactant solution. Ultraviolet-visible-near-infrared radiation absorption spectroscopy was employed to monitor the aggregation of SWCNTs. The results demonstrated that individually dispersed SWCNTs were more toxic than SWCNT aggregates toward bacteria (gram-negative Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
416
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(442 citation statements)
references
References 59 publications
25
416
1
Order By: Relevance
“…These results are in accordance with those of Arias and Yang, and Liu et al, although those experiments were conducted differently and substrates were formulated differently. 59,60 The same observation was reported by Dong et al where single-walled carbon nanotube (SWCNT) tests indicated that the nanotube concentration is the deciding factor for an antibacterial effect. 61 Our results showed that increasing the MWCNT concentration (from 10 to 100 µg mL -1 ) led to increases in the bactericidal effect against E. coli and S. aureus, and these results are very similar to those observed in a study by Liu et al, which reported that the death rate of E. coli increased with an increase in SWCNT concentration from 5 to 80 µg mL…”
Section: Bactericidal Propertiessupporting
confidence: 68%
“…These results are in accordance with those of Arias and Yang, and Liu et al, although those experiments were conducted differently and substrates were formulated differently. 59,60 The same observation was reported by Dong et al where single-walled carbon nanotube (SWCNT) tests indicated that the nanotube concentration is the deciding factor for an antibacterial effect. 61 Our results showed that increasing the MWCNT concentration (from 10 to 100 µg mL -1 ) led to increases in the bactericidal effect against E. coli and S. aureus, and these results are very similar to those observed in a study by Liu et al, which reported that the death rate of E. coli increased with an increase in SWCNT concentration from 5 to 80 µg mL…”
Section: Bactericidal Propertiessupporting
confidence: 68%
“…After thorough washing with CB, samples were dehydrated in a series of ethanol solutions (10-100 %). The samples were dried, mounted on aluminum stubs with conductive carbon cement, and finally coated with a gold film for observation under FESEM (Hitachi 4800 SEM at 1.5 kV) (Liu et al 2009). For CLSM, after initial through washing, the biofilm was covered with 50 lL of 100 lg/ml of dye, concanavalin A, alexaflour 488, and incubated for 30 min at 4°C.…”
Section: Biofilm Assaymentioning
confidence: 99%
“…With mixture of the SYTO 9® and propidium iodide (PI), bacteria with intact cell membranes stain fluorescent green (considered to be viable), and bacteria with compromised membranes stain fluorescent red (considered to be nonviable). Similar fluorescence dye methods have been applied in other studies monitoring the antibacterial properties of nanoparticles (Liu et al, 2009;Perreault et al, 2015;Raghupathi et al, 2011).…”
Section: Bacterial Cell Viability Assaymentioning
confidence: 98%
“…In general, bacterial deactivation can be the result of: 1) direct mechanical breakage of outer cell membranes by sharp edged nanoparticles (Akhavan and Ghaderi, 2010;Liu et al, 2009;Situ and Samia, 2014); 2) chemical oxidative stress mediated cell injury that is induced by in situ production of reactive oxygen species (Krishnamoorthy et al, 2012;Su et al, 2009); and 3) dehydration of cell membrane (Beney et al, 2004). It is highly likely that the latter two bacterial deactivation mechanisms are at play when wastewater is exposed to Fe 3+ -saturated montmorillonite.…”
Section: Spectroscopy Evidence Of Bacterial Cell Deactivation On Fe 3mentioning
confidence: 99%